Oral manifestations in myeloproliferative diseases: A literature review (Research, Society and Development, 2021)
Objective: to address the manifestations caused by the alterations caused by the various myeloproliferative diseases in the oral cavity and the implications in the patient's life, in order to provide a theoretical basis that helps in the early diagnosis and therapy of these pathologies. Materials and Methods: this is a literature review where a search was carried out in the databases related to the areas of Health such as: SCIELO, PUBMED and LILACS using time cut from 2016 to 2020, with the descriptors "hematology" or "diseases hematological "; "affection" or "oral manifestations" and "leukemia" or "hematological changes". Discussion: The present work is related to oral changes caused by myeloproliferative diseases, where there are few reports of these changes in the literature, since there was no knowledge of the involvement of the oral cavity with diseases, in an attempt to improve this differential diagnosis. This work brings the main alterations found in the literature on oral alterations. Conclusion: With this, the need for multidisciplinary monitoring of patients affected by these diseases is evident and it is hoped that this research, together with future research, can clarify the changes caused by myeloproliferative diseases, especially their manifestations in the oral cavity, for a differential diagnosis and precocious. Thus, we conclude that there is a direct relationship between clinical changes in the oral cavity in individuals with myeloproliferative disease.